Two Perspectives on E-Learning Design: A Synopsis of a U. S. and a European Analysis - Hillen, Stefanie A.; Landis, Melodee (International Review of Research in Open and Distributed Learning, 2014)
This article seeks to examine e-learning design arising from two educational traditions: the United States of America and Europe. The research question is: Broadly, what kinds of pedagogy, instructional design models, or didactical models are established and proposed for e-learning design on the two continents? Two researchers examined multiple articles and texts in an effort to discern the prominent approaches in their respective regions. The analysis is tripartite: First, the educational philosophies, which have guided e-learning design on each continent, will be presented; second, specific theories about learning influencing e-learning design will be discussed; and finally, e-learning design, which arises from innovative instructional strategies, will be investigated. The resulting analysis brings to the surface not only how the values that underpin e-learning development in each region differ but also how specific perspectives influence the respective fields. The researchers acknowledge these differences but also remark on the historic and contemporary symbiosis that has endured even in this relatively new field of e-learning.